The Jewish world of Alexander Hamilton - Porwancher, Andrew (Princeton University Press, 2021)
"In his hit musical "Hamilton," Lin-Manuel Miranda paints Founding Father Alexander Hamilton as the ultimate outsider, the "bastard, orphan, son of a whore," who by sheer grit and smarts achieves political greatness, leaving a permanent mark on the American landscape as the architect of its financial system. In this book Andrew Porwancher argues that the first Secretary of the Treasury and chief author of "The Federalist Papers" was even more of an outsider than previous biographers have noted. Porwancher has uncovered evidence strongly suggesting that Hamilton was born and raised as a Jew - at least until the age of 13, when his mother died. The evidence is not definitive, but it is compelling. Porwancher's story begins in the 1750s in a colony in the Danish West Indies, where Hamilton's mother, Rachel Faucette, married a merchant named Johann Michael Levine, who sometimes went by the name of Lavien, a Sephardic version of Levine. Porwancher is convinced that Levine was Jewish and that Rachel -- born to a Christian family in the British Caribbean -- converted in order to marry him, as was required by Danish law at the time. Faucette's marriage with Levine was troubled, leading her to flee to a nearby British Caribbean colony where she met the Scotsman James Hamilton, who conceived with her the future Founding Father out of wedlock. Assuming Faucette's conversion to Judaism before this birth, Alexander Hamilton was thus born a Jew, according to Jewish law. What is more, there is strong evidence that he was raised with a Jewish education, as he attended a Jewish day school on the island colony of Nevis at least until the age of 13, the year of his mother's death. (It is noteworthy that he is not listed in the island's baptismal records -- although parish records from that era are fragmentary and thus cannot provide definitive conclusions.) At some point, Hamilton began identifying as a Christian, at least by the age of 17, when he arrived in New York. Although as an adult he wrote copiously on seemingly every topic under the sun, he maintained a studied silence about his West Indian -- and, most likely, Jewish -- origins. This is understandable, for without the pretence of a Christian background it is unlikely that the young Hamilton could have advanced socially and professionally in the British colonies to the north. And yet, as Porwancher argues, Hamilton's connections to Jews and Judaism continued throughout his life. During a long professional life as a practicing lawyer and public figure he defended Jewish rights. Notably, he spoke out against antisemitism and ensured that a Jew be appointed to the board of his alma mater, Columbia University - the first Jew on the board of any American college. And although a nominal Christian, Hamilton kept institutional Christianity at arms length throughout his life. (There is no record of him mentioning the church or taking communion.) Porwancher does not overstate his claims, nor does he try to simplify the fact that the lines between Jewish and non-Jewish identity were frequently blurred in the Caribbean world that into which Hamilton was born. What this book does, in the words of the author, is add "the relevance of Judaism to our already rich understanding of Hamilton.""-- Provided by publisher.
Keywords: Hamilton, Alexander, -- 1757-1804 -- Religion.; Hamilton, Alexander, -- 1757-1804; Protestantism -- Social aspects -- United States -- History -- 17th century.; Judaism -- Social aspects -- United States -- History -- 17th century.; Judaism -- Social aspects -- Saint Kitts and Nevis -- Nevis -- History -- 17th century.; Statesmen -- Religious life -- United States -- History -- 18th century.; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1809.; New York (N.Y.) -- Biography.; Nevis -- Biography.; Protestantisme -- Aspect social -- États-Unis -- Histoire -- 17e siècle.; Judaïsme -- Aspect social -- États-Unis -- Histoire -- 17e siècle.; Judaïsme -- Aspect social -- Saint Kitts et Nevis -- Nevis -- Histoire -- 17e siècle.; Hommes d'État -- États-Unis -- Vie religieuse -- 18e siècle.; États-Unis -- Politique et gouvernement -- 1775-1783.; États-Unis -- Politique et gouvernement -- 1783-1809.; HISTORY / United States / Revolutionary Period (1775-1800); POLITICAL SCIENCE / History & Theory.; Judaism -- Social aspects; Politics and government; Religion; Statesmen -- Religious life; New York (State) -- New York; Saint Kitts and Nevis -- Nevis; United States; 1600-1809; Biographies; History